Development of a mocha-flavored peanut spread - Aranilla, Asteria Cherrie A. (2001.)
Five formulations of mocha-flavored peanut spread were prepared by mixing different levels of mocha powder (2%, 4%, 6%, 8% and 10%) into peanut spread. The levels of sugar (20%) and stabilizer (1%) added were the same for each formulation. Hedonic responses of fifty untrained panelists to the formulations were obtained. The samples were evaluated for color, mocha flavor, sweetness, spreadability and overall acceptability using a 9-point hedonic scale. Results indicated that there were significant differences at 5% level of significance between the formulations in all the attributes except for sweetness. The mocha-peanut spread samples varied from brown to slightly dark brown in color with slightly weak to slightly distinct mocha flavor as perceived by the panelists. Sweetness and spreadability ranged from just right to moderate. The formulation with 10% mocha powder got the highest mean score of 6.86 for overall acceptability, which corresponds to a rating between like to like moderately. This rating indicated that using the correct formulation could produce an acceptable mocha-flavored peanut spread.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peanut products